2007
DOI: 10.1007/s00011-007-7111-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pyrethroids and piperonyl butoxide on histamine release from isolated rat mast cells

Abstract: The results relating to mast cell histamine release reveal both similarities and differences with the influence of the pyrethroids on cell membrane activities. They indicate that not solely membrane interactions but also additional or alternative targets are involved in the effects of pyrethroids on mammalian tissues. Moreover, the pronounced effects of a brief cell exposure suggest that long-term exposure can be hazardous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Due to their many advantages, it is very important to research the biological effects of pyrethroid insecticides, which are included the Karate Zeon. Previous studies have reported their toxicity on living organisms (Grossman 2007, Surralles et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their many advantages, it is very important to research the biological effects of pyrethroid insecticides, which are included the Karate Zeon. Previous studies have reported their toxicity on living organisms (Grossman 2007, Surralles et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Another pyrethroid, metofluthrin, is particularly vapor-active against insects and mosquitoes for both indoor and outdoor use [ 57 , 58 ]. Pyrethroids are neurotoxic, possibly by disturbing the membrane function of neuronal cells [ 59 ]. The possible genotoxicity of transfluthrin and metofluthrin was detected by SMART, with transfluthrin (up to 0.103 mg/mL) and metofluthrin (up to 60 μg/mL) as a mutagen and recombinogen, respectively.…”
Section: Applications Of Smart For Genotoxicity Assessment Of Environmental Pollutantsmentioning
confidence: 99%
“…Various combination toxicity studies were earlier performed on synthetic pyrethroids, but the data regarding the toxicological effects of PBO and tetramethrin addition into the synthetic pyrethroid formulations are very limited, and most of them were obtained from in vitro studies (Diel et al, 1999; Grosman, 2007; Grosman and Diel, 2005; Matoba et al, 1998a, 1998b; Meacham et al, 2008; Motomura and Narahashi, 2001). In this regard, the aim of the present study was to investigate the effects of the synergist PBO and the knockdown agent tetramethrin combinations on the 28-day subacute oral toxicity of the synthetic pyrethroids cypermethrin, alphacypermethrin, and deltamethrin in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%